VD_FINDINFO HC / 2016 / 406 vom 1. März 2016 - VD Tribunal cantonal (2016)
DROIT D'EMPTION, POUVOIR DE REPRÉSENTATION, COMMUNE, LIMITATION AUX CONCLUSIONS DES PARTIES | 55 CC, 4 al. 1 ch. 6 LC, 67 al. 1 LC, 68 LC, 55 al. 1 CPC (CH), 58 al. 1 CPC (CH)